PORTAL HYPERTENSION: AN AYURVEDIC VIEW - Patil Siddanagouda. A; Kurabet Raviraj. S; Kulkarni Veena. S (International Journal of Applied Ayurved Research, 2017)
Portalcaval Anastomosis is a specific type of anastomosis that occurs between the veins of portal circulation and those of systemic circulation. Portal hypertension is defined as sustained elevation of portal pressure more than 12 mm Hg. The mechanism behind causation of portal hypertension are two, (1) increased intrahepatic resistance to the passage of blood flow through the liver due to cirrhosis and (2) increased splanchnic blood flow secondary to vasodilation within the splanchnic vascular bed. Portal hypertension is directly responsible for the two major complications of cirrhosis: variceal hemorrhage and ascitis. These varices develop at sites where the systemic and portal circulations have common capillary beds. The principal sites are oesophageal varices, haemorrhoides, caput medusa and retroperitoneal anastomoses. The development of oesophago-gastric varices which is frequently manifested by massive haematemesis is the most important consequence of portal hypertension. Bleeding from haemorrhoids is usually not as serious a complication as haematemesis from oesophageal varices. Similar concept has been explained in our classics in the context of Raktapitta. Here an effort is made to understand the Ayurvedic concept of Portal Hypertension.